VCT (VALUE CLARIFICATION TECHNIQUE) LEARNING MODEL APPLICATION TO IMPROVE HISTORICAL VALUE UNDERSTANDING - Suryani, Nunuk (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2010)
Learning the history referred to as the transfer of value. The role of history education is very important in teaching about values, moral and spiritual. By internalizing these values will be formed nationalism in student attitudes. Establishment of nationalistic attitude is important to anticipate the global challenges and a variety of shocks that hit the disintegration of Indonesia recently. Historical experience proves the attitude of nationalism can generate social dynamics in the past. Education history can be said to have educational value if the history of education can contribute to make students become someone who has a wise attitude or have a noble moral values. For history has educative function, then the teacher can make learning history with a moral approach. Moral approach is an approach that emphasizes the value of the meaning contained in the material presented history. Students should be actively involved in learning activities. In order to more meaningful learning history or high value, teachers can use the methods that can internalize the values in it. One is the model of value clarification. Value clarification learning model first used by Louis Raths in the 1950s while teaching at New York University. VCT learning model (Value Clarification Technique) is a “learning model which to assist students in finding and determining a value that is considered good in dealing with problems through the process of analyzing the existing value in the self-student. This approach will help students understand and find value / meaning of historical events in depth (ultimate meaning). Based on the data analysis it is found that the VCT model to produce an understanding of history better than the conventional models. Students with high emotional quotient have the understanding of historical value better than students with low emotional quotient.